Sequential surgery following conversion therapy based on combination of immune checkpoint inhibitors and antiangiogenic targeted drugs as a potential approach for advanced hepatocellular carcinoma with portal vein tumor thrombus: a prospective study - Gao, Shang; Hu, Yanqin; Cao, Yinbiao; Liu, Weizheng; Jiang, Hongxiang; Jiang, Tong; Tang, Haowen; Lu, Shichun (Journal of Gastrointestinal Oncology, 2026)
Background: This study aims to evaluate the long-term efficacy and safety of hepatocellular carcinoma (HCC) patients with portal vein tumor thrombus (PVTT) receiving sequential surgery following conversion therapy with a combination of targeted therapy and immunotherapy, thereby demonstrating the therapeutic potential of this regimen.Methods: Data from 76 HCC patients with PVTT treated with programmed death-1 (PD-1) inhibitors and tyrosine kinase inhibitors (TKIs) followed by surgical treatment at Chinese PLA General Hospital (June 2019 to June 2024) were analyzed. Recurrence-free survival (RFS) and overall survival (OS) were primary endpoints.Results: The median RFS was 21 months; the median OS was 62 months. RFS rates at 6 months, 1 year, 2 years, and 3 years were 76.2%, 59.7%, 48.1%, and 42.5%, respectively. OS rates at 6 months, 1 year, 2 years, 3 years, and 5 years were 98.7%, 93.4%, 78.1%, 72.4%, and 45.5%, respectively. Cox regression showed that preoperative alpha-fetoprotein (AFP) ≥20 ng/mL was an independent mortality factor, while non-major-pathological-response (non-mPR) and tumor size >50 mm were independent recurrence factors. Adverse events and surgical complications were evaluated, with no patient deaths resulting from conversion therapy or sequential radical surgery.Conclusions: For HCC patients with PVTT who achieve successful conversion and undergo radical surgery, sequential surgery following conversion therapy based on combination of immune checkpoint inhibitors (ICIs) and anti-angiogenic targeted drugs (AATDs) is associated with favorable RFS and OS, and appears safe and effective. These findings suggest that this regimen may represent a promising option for these patients.